COMPARISON OF PHYSICAL EDUCATION TEACHERS' LEADERSHIP PROFILE IN THE PUBLIC AND PRIVATE ELEMENTARY SCHOOL STUDENTS' VIEW IN MONTES CLAROS (Fiep Bulletin - online, 2015)
The present study aims at identifying and comparing the Physical Education teacher's leadership profile before his/her students at public and private elementary schools in the city of Montes Claros (MOC). The leader must integrate well with the other members of the group aware that those being led choose their leader for seeing in him/her the possibility of having their needs fulfilled. The efficacy of a leader's actions depends on such elements as personal relations, task structure and the leader's power. In this research 160 students, being 80 from public schools (51.67% males and 48.33% females, mean age 13± 1.93 years) and 80 from private schools (58.75% males and 41.25% females, mean age 12± 1.41 years), randomly chosen, answered the questionnaire about the leadership profile. The instrument consists of 40 objective items related to the ideal sports teacher/coach's behavior, which uses Likert scale of 0 to 4 points. At public schools, training-instruction dimension mean was 230, social support 212, reinforcement 224, democratic 205 and autocratic 213, whereas at private schools, training-instruction dimension mean was 194, social support 189, reinforcement 195, democratic 188 and autocratic 187. In the comparison among the 5 leadership dimensions between public and private schools, there were statistically significant differences only in the training-instruction and democratic dimensions (p=0.05), being the Physical Education teacher's leadership profile in the public school students' view dominantly characterized in the training-instruction dimension, mean 230 and at  private schools in the reinforcement dimension, mean 195.
Keywords: Leadership; schools; Physical Education